Bramble and Maggie give and take - Haas, Jessie; Friend, Alison (Somerville, MA Candlewick Press, 2013)
"Bramble the horse is starting life with her new person, Maggie. When Maggie wants to go for a ride, Bramble is hesitant because she feels that neither she nor Maggie should be boss all the time. There should be some give-and-take. Maggie agrees, and a carrot seals the deal."--Dust jacket
Give and take -- Too quiet -- Sshhoosshhh! -- The hen
Keywords: Friendship -- Juvenile fiction; Horses -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Friendship -- Fiction; Horses -- Fiction; Human-animal relationships -- Fiction